Archetype models upscale understanding of natural pest control response to land‐use change. Issue 8 (18th September 2022) - Alexandridis, Nikolaos; Marion, Glenn; Chaplin‐Kramer, Rebecca; Dainese, Matteo; Ekroos, Johan; Grab, Heather; Jonsson, Mattias; Karp, Daniel S.; Meyer, Carsten; O'Rourke, Megan E.; Pontarp, Mikael; Poveda, Katja; et al.
Abstract: Control of crop pests by shifting host plant availability and natural enemy activity at landscape scales has great potential to enhance the sustainability of agriculture. However, mainstreaming natural pest control requires improved understanding of how its benefits can be realized across a variety of agroecological contexts. Empirical studies suggest significant but highly variable responses of natural pest control to land‐use change. Current ecological models are either too specific to provide insight across agroecosystems or too generic to guide management with actionable predictions. We suggest obtaining the full benefit of available empirical, theoretical, and methodological knowledge by combining trait‐mediated understanding from correlative studies with the explicit representation of causal relationships achieved by mechanistic modeling. To link these frameworks, we adapt the concept of archetypes, or context‐specific generalizations, from sustainability science. Similar responses of natural pest control to land‐use gradients across cases that share key attributes, such as functional traits of focal organisms, indicate general processes that drive system behavior in a context‐sensitive manner. Based on such observations of natural pest control, a systematic definition of archetypes can provide the basis for mechanistic models of intermediate generality that cover all major agroecosystems worldwide. Example applications demonstrate the potential for upscaling understanding and improving predictions of natural pest control, based on knowledge transfer and scientific synthesis. A broader application of this mechanistic archetype approach promises to enhance ecology's contribution to natural resource management across diverse regions and social‐ecological contexts.